PEPTIDE SURFACTANT FOR EOR APPLICATION - Usman Usman (Scientific Contributions Oil and Gas, 2015)
Motivated by recent advances on the peptides surfactants that capable of forming emulsion stabilization by lowering the interfacial tension, an extensive set of tests were carried out to further investigate the applicability of peptide molecules for enhanced oil recovery application. A designed peptide surfactant using protein biotechnology approach was laboratory tested at three samples representing the different oil characteristics, water formation, and reservoir rock. The best performance of peptide surfactant obtained is of sample A. Peptide surfactant is able to form microemulsion Type III at pH 11. It can lower the interfacial tension value until the range of 10-2 dyne/cm at 25°C, even though itsn’t reached the desired target yet which is 10-3 dyne/cm or even less. It can also change rock wettability from water wet into strong water wet. Sample A has relatively short hydrocarbon chain compared to samples B and C, it is classifi ed as intermediate oil, medium salinity for water formation, and rock mineral is dominated with quartz without gypsum that is very harmful to the fuction of surfactant. The developed peptide surfactant hasn’t been stable at high temperature yet. When tested at 70°C, the interfacial tension value increase to around 10-1 dyne/cm. Displacement effi ciency using oil sample A is less than 1%. Based on these results, the next peptide surfactant design will be focused on resistance capability improvement to temperature and peptide amino acid structure position to produce the better result of surfactant. The performance test results of peptide surfactant presented in this paper is valuable in designing specifi c peptide surfactant for certain oil fi eld.